Advanced Database Indexing - Manolopoulos, Yannis; Theodoridis, Yannis; Tsotras, Vassilis (Springer US, 2000)
Advanced Database Indexing begins by introducing basic material on storage media, including magnetic disks, RAID systems and tertiary storage such as optical disk and tapes. Typical access methods (e.g. B+ trees, dynamic hash files and secondary key retrieval) are also introduced. The remainder of the book discusses recent advances in indexing and access methods for particular database applications. More specifically, issues such as external sorting, file structures for intervals, temporal access methods, spatial and spatio-temporal indexing, image and multimedia indexing, perfect external hashing methods, parallel access methods, concurrency issues in indexing and parallel external sorting are presented for the first time in a single book. Advanced Database Indexing is an excellent reference for database professionals and may be used as a text for advanced courses on the topic
Keywords: Data Structures and Information Theory; Information Storage and Retrieval; Memory Structures; Data structures (Computer science); Information storage and retrieval; Computer memory systems